2015
DOI: 10.1364/oe.23.004867
|View full text |Cite
|
Sign up to set email alerts
|

Coherent amplification of attosecond light pulses in the water-window spectral region

Abstract: ]. La impressió o còpia electrònica es poden fer només per a ús personal . La reproducció, la distribució, la duplicació amb finalitats comercials i la modificació de continguts queden prohibides.Serrat, C., Roca, D., Seres, J. (2015) Abstract: We present a theoretical study on coherent extreme ultraviolet (XUV) attosecond pulse amplification mediated by nonlinear parametric enhanced forward scattering occurring in the interaction of a strong femtosecond infrared (IR) laser pulse combined with a weak attosec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…Our study corroborates previous 232 theoretical work performed under the SFA [11,13,14]. We 233 conclude that several parameters are decisive and need to be 234 balanced for IXPA processes to arise, such as the peak intensity 235 of the driving IR pulse, the ionization potential of the medium, 236 and the duration and spectral contents of the weak XUV-x-ray 237 seed pulses.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Our study corroborates previous 232 theoretical work performed under the SFA [11,13,14]. We 233 conclude that several parameters are decisive and need to be 234 balanced for IXPA processes to arise, such as the peak intensity 235 of the driving IR pulse, the ionization potential of the medium, 236 and the duration and spectral contents of the weak XUV-x-ray 237 seed pulses.…”
supporting
confidence: 78%
“…In previous research we addressed the influence of weak 23 XUV radiation pulses of photon energies far from the 24 ionization potential of the medium added to the strong IR 25 driving pulse in HHG processes [11,13,14,16,17]. In particular, 26 we showed that forward scattering can be largely enhanced 27 when an XUV pulse is optimally synchronized with the IR 28 pulse [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond independent theoretical [18] and experimental [25] demonstration, in the present work we show large agreement between theoretical and experimental observations concerning amplification by avalanche of a XUV attosecond pulse train in an He gas amplifier at the 110 eV region. The simulations show that the ionization potential of the gas [19] and the consequent dispersion caused by the free electrons in the amplifying medium are key factors to produce XUV amplification in a specific spectral region.…”
Section: Introductionmentioning
confidence: 99%
“…Such nonlinear interactions, as X-ray parametric amplification (XPA), can cause amplification of the XUV pulse in the gas medium. Both nonlinear enhanced ionization and stimulated amplification have been theoretically studied, namely, a XUV seed pulse was shown to produce new harmonic lines [14], and it was shown to be amplified by backward scattering [15] or forward scattering [16][17][18][19][20]. Parametric amplification processes have been recently measured and described also by perturbative highorder parametric interaction [21] and by ab initio simulations in hydrogen molecular ions [22].…”
Section: Introductionmentioning
confidence: 99%